2016
DOI: 10.1515/bmt-2014-0172
|View full text |Cite
|
Sign up to set email alerts
|

Entropy at the right atrium as a predictor of atrial fibrillation recurrence outcome after pulmonary vein ablation

Abstract: Atrial fibrillation (AF) recurrence rates after successful ablation procedures are still high and difficult to predict. This work studies the capability of entropy measured from intracardiac recordings as an indicator for recurrence outcome. Intra-atrial recordings from 31 AF patients were registered previously to an ablation procedure. Four electrodes were located at the right atrium (RA) and four more at the left atrium (LA). Sample entropy measurements were applied to these signals, in order to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Certainly, the results described showed differences in shannon entropy between both atria in recurrent and nonrecurrent AF group, but with higher atrial gradient in the patients that maintenance sinus rhythm. Previous studies have showed that patients that remained in sinus rhythm presented different entropy values tan those who turned back to AF [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Certainly, the results described showed differences in shannon entropy between both atria in recurrent and nonrecurrent AF group, but with higher atrial gradient in the patients that maintenance sinus rhythm. Previous studies have showed that patients that remained in sinus rhythm presented different entropy values tan those who turned back to AF [14].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the dominant atrial frequency has been described as a predictor of AF ablation outcome, where long cycle lengths were responsible for the organization of the arrhythmia, whereas the shortest cycle lengths were related to recurrences [12]. Based on mechanistic studies, rotor sites are expected to exhibit greater electrical periodicity, unique spectral characteristics such as higher dominant frequency [13], and higher entropy [14,15], distinguishing them from other atrial sites [16]. Dominant frequency from atrial signals extracted with MSPCA showed a differences in left atrium main frequency in the left atrium with a more rapid activity in the patients with recurrences in the arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…The high-DF sites produce a favourable condition for maintenance of AF [16]. Based on mechanistic studies, these areas exhibit higher dominant frequency [17], higher entropy [18] and lower causality from the pulmonary veins to the atria [19], distinguishing them from other atrial sites [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high dominant atrial frequency sites are reported to be related to the center of a focal-firing rotor or local reentry circuit, producing a favourable condition for maintenance of AF [11]. Based on mechanistic studies, rotor sites are expected to exhibit greater electrical periodicity, unique spectral characteristics such as higher dominant frequency [12], and higher entropy [13] and lower causality from the PV to the atria [14].…”
Section: Discussionmentioning
confidence: 99%